Real-Time Animation, AI and Virtual Production: Opportunities and Challenges : And how to build a low-budget ICVFX stage - Schoenau-Fog, Henrik; Hussain, Aishah; Thomsen, Mathias Ramsø (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
This paper explores the opportunities of utilizing real-time animation and AI in Virtual Production (VP) workflows. The investigation is based on insights from the ViZARTS project, where filmmakers, TV producers and animations are educated during hands-on workshops to utilize the potential of VP. The study will describe some of the challenges we have encountered and introduce a few innovative workflows, we have developed during the workshops, including how to build a low-budget sustainable VP training facility studio. Finally, we will look ahead and discuss the future of real-time animation and AI-driven workflows in Virtual Production.